2018
DOI: 10.1186/s12875-018-0770-1
|View full text |Cite
|
Sign up to set email alerts
|

Views of family physicians on heterosexual sexual function in older adults

Abstract: BackgroundSexual functioning among older adults has received little attention in research and clinical practice, although it is an integral part of old age. As older adults tend to consume health services and to visit family physicians more frequently, these care-providers serve as gatekeepers in the case of sexual concerns. The present study evaluated the perceptions of family physicians regarding sexuality in older adults.MethodQualitative interviews with 16 family physicians were conducted. We used in-depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 73 publications
(92 reference statements)
0
33
0
5
Order By: Relevance
“…Family physicians’ perceived the men’s problems as simple and easily solved using medication, while the women’s problems were perceived as more complex, requiring a solution including both medication as well as emotional support. This is in spite of the fact that other studies indicate that men’s sexual function is related to their psychological state [10,15,2830]. The physicians’ perspectives reflect the patients’ attitudes; there is a clear public preference for treatment in the form of medication.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Family physicians’ perceived the men’s problems as simple and easily solved using medication, while the women’s problems were perceived as more complex, requiring a solution including both medication as well as emotional support. This is in spite of the fact that other studies indicate that men’s sexual function is related to their psychological state [10,15,2830]. The physicians’ perspectives reflect the patients’ attitudes; there is a clear public preference for treatment in the form of medication.…”
Section: Discussionmentioning
confidence: 94%
“…It was also was found that physicians who treat women with gynaecological symptoms identify a difficulty in sexual function, but very few physicians discuss this matter with the women [27]. These findings emphasize that also among women, there are medical reasons for sexual function difficulties, but these problems receive less attention and treatment [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, research showed that both primary care physicians and nurses working in long term care tend not to address sexual health proactively when with older adults, as they feel it is not a legitimate topic to discuss with this age group and are afraid to offend their patients [57,58]. Additionally, primary care physicians tend to look at sexual health in older age in the context of dysfunctions or diseases [59] and consequently discuss sexuality mostly in conjunction with other medical conditions [60]. It seems health care workers, although theoretically recognising that sexuality plays an important role in the lives of older adults, are responding to stereotypes of the 'asexual older adult' [57,58], an image that is often portrayed in the media and has become a wide societal image [61][62][63].…”
Section: Health Care Workers' Response To Sexual Health Needs Of Oldementioning
confidence: 99%